Late medieval catholicism and the impact of the Reformation in the Deanery of Derby, c.1520 to c.1570 - D'Arcy, Joan (1996)
The question of the effects of the English Reformation is a matter of on-going and lively debate. This thesis hopes to illuminate this question in some small measure, by examining the deanery of Derby, an ecclesiastical unit within the diocese of Coventry and Lichfield. Although the focal point is the deanery, it is set within the wider context of sixteenth century England. Past research on the Reformation in Derbyshire has been brought together, reviewed and expanded through a study of Reformation papers and other ecclesiastical, political and legal records, both state and diocesan. An analysis of about 700 wills has also been undertaken and their use examined in the light of recent doubts cast upon their validity as source material for analysis of religious belief. Chapter One sets out the parameters of the study and its aims. The deanery is then described and set in the context of governing episcopal and lay authorities. Chapter Two examines the state of the pre-Reformation secular church while Chapter Three does the same for the religious orders and finds that both tended to be conservative. The first three chapters provide a base line for a consideration of the effects of religious change. Chapter Four draws on evidence from wills to address the impact of Henrician legislation on religious belief and practice. In Chapter Five the dissolution of the monasteries in Derbyshire is traced. Chapter Six examines the theme of a Mid-Tudor crisis between 1547 and 1558 and parochial reactions to the increasingly reformist policies of Edward VI's reign and subsequent reversal of policy in the reign of Mary I. The conclusion is drawn that, in general, there was a slow response to reformist legislation. Chapter Seven examines the material consequences of religious change as it affected the local gentry and assesses their success in the expanded land market. Chapter Eight argues that, religious changes led to considerable local instability. The question of continuity or revival of catholicism is the main question of Chapter Nine which finds that there was a high degree of catholic continuity and some gentry involvement in conspiracy. Chapter Ten draws the conclusion that the Reformation gave rise to deep divisions which had religion as a root cause.